Studi Kasus Pasangan Hubungan Jarak Jauh Dalam Membangun Ketertarikan Interpersonal Pada Dasar Afektif - Chiisai, Ayu Putri; Mumpuni, Sesya Dias (Jurnal Bimbingan dan Konseling Pandohop, 2021)
Long distance relationship is a relationship that occurs in couples when one of them has to move to study or work resulting in their relationship adapting to changes, namely long distance relationships. Long distance relationships have a sense of caring for each other's feelings so they spend time communicating. Communication problems sometimes occur which can affect their partner's emotions, both positive and negative. This study examines how long distance relationship couples build their interpersonal attraction on an affective basis. The research subjects were 2 couples with a total of 4 respondents to find out their efforts in building attraction to each other. The research used interview method with the aim of research to find out their efforts in maintaining long distance relationships by building their interpersonal interest on the affective basis, namely positive and negative emotions that arise from problems.